Exercice 2 ( 6 points) 1. Soit \( f \) la fonction définie par la relation : \( f(x)=x^{2}-x+2 \). a. Etablir, pour tout \( h \in R \),: \( \frac{f(2+h)-f(2)}{h}=3+h \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
Pour prouver que \( \frac{f(2+h)-f(2)}{h}=3+h \), commençons par calculer \( f(2) \). En substituant \( x = 2 \) dans \( f(x) \) : \[ f(2) = 2^2 - 2 + 2 = 4 - 2 + 2 = 4. \] Ensuite, calculons \( f(2+h) \) : \[ f(2+h) = (2+h)^2 - (2+h) + 2 = (4 + 4h + h^2) - (2 + h) + 2 = h^2 + 3h + 4. \] Maintenant, calculons la différence \( f(2+h) - f(2) \) : \[ f(2+h) - f(2) = (h^2 + 3h + 4) - 4 = h^2 + 3h. \] Pour finir, formons le rapport : \[ \frac{f(2+h) - f(2)}{h} = \frac{h^2 + 3h}{h} = h + 3. \] Ainsi, pour tout \( h \in R \), nous avons bien établi que : \[ \frac{f(2+h) - f(2)}{h} = 3 + h. \]